METODE FTIR PADA KARAKTERISASI MISELIUM JAMUR TIRAM PUTIH DENGAN BIBIT BERMEDIA SORGUM - Ana Fitriana; Fitrah Hadi Firdaus; Irlian Nurmaniah; Maya Risanti; Mersi Kurniati; Irzaman Irzaman (Program Studi Pendidikan Fisika dan Program Studi Fisika Universitas Negeri Jakarta, LPPM Universitas Negeri Jakarta, HFI Jakarta, HFI, 2015)
Oyster mushroom’s mycelium was inoculated by sorgum media’s seed were done. FTIR analisys in 400-4000 cm-1 of wave length showed that oyster mushroom’s mycelium possessed of O-H, C-H, C-O, and C=O molecul. O-H molecul showed β-glucan and C-H, C-O, and C=O molecul showed aldehyd, ester, and keton cluster. Keywords: cluster, FTIR, mycelium, oyster mushroom, sorgum.